The Significance of Everyday Access to Justice in Myanmar's Transition to Democracy - Kyed, Helene Maria (ISEAS - Yusof Ishak Institute, 2019)
Legal pluralism in Myanmar is a reality that is not sufficiently recognized. A lack of recognition of and clear mandates for the informal justice providers, along with the absence of coordination between these providers and the judiciary, present critical challenges to local dispute resolution and informal legal systems.